2019
DOI: 10.1038/s41467-018-07907-2
|View full text |Cite
|
Sign up to set email alerts
|

The non-canonical SMC protein SmcHD1 antagonises TAD formation and compartmentalisation on the inactive X chromosome

Abstract: The inactive X chromosome (Xi) in female mammals adopts an atypical higher-order chromatin structure, manifested as a global loss of local topologically associated domains (TADs), A/B compartments and formation of two mega-domains. Here we demonstrate that the non-canonical SMC family protein, SmcHD1, which is important for gene silencing on Xi, contributes to this unique chromosome architecture. Specifically, allelic mapping of the transcriptome and epigenome in SmcHD1 mutant cells reveals the appearance of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
141
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(157 citation statements)
references
References 75 publications
14
141
1
1
Order By: Relevance
“…We propose that Smchd1 plays a role in protecting the repressed imprinted genes from inappropriate activation. We and others have previously found that cells without Smchd1 have increased Ctcf binding (26,35,36). At Sm-chd1-sensitive imprinted genes we have found increased H3K4me2 or H3K4me3 (26,29).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…We propose that Smchd1 plays a role in protecting the repressed imprinted genes from inappropriate activation. We and others have previously found that cells without Smchd1 have increased Ctcf binding (26,35,36). At Sm-chd1-sensitive imprinted genes we have found increased H3K4me2 or H3K4me3 (26,29).…”
Section: Discussionsupporting
confidence: 56%
“…We have discovered Smchd1 is a novel maternal effect gene required for genomic imprinting. Recently, we and others discovered that zygotic Smchd1 mediates long-range chromatin interactions at its target genes, both imprinted regions and elsewhere in the genome (28,35,36). Based on the data presented here, we propose that Smchd1 is required to translate germline imprints into a chromatin state required to silence expression at select imprinted clusters.…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…Furthermore, it contains a GHKL (gyrase, Hsp90, histidine kinase, MutL)-type ATPase rather than the bipartite ABC-type ATPase domain typically seen in SMC proteins (Brideau et al, 2015). Several studies implicate roles of SMCHD1 in modulating chromosome architecture at the inactive X chromosome and at Hox clusters (Nozawa et al, 2013;Jansz et al, 2018;Wang et al, 2018;Gdula et al, 2019). SMCHD1 mediates the compaction of the inactive X chromosome in females linking the H3K9me3 and the XIST-H3K27me3 domains (Nozawa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%